2004
DOI: 10.1182/blood-2003-06-2124
|View full text |Cite
|
Sign up to set email alerts
|

The WHO classification of MDS does make a difference

Abstract: The purpose of this study was to determine the facility and reliability of the World Health Organization (WHO) classification of myelodysplastic syndromes (MDSs) with several observers reviewing the same diagnostic specimens. We also wanted to determine if the WHO classification provided additional information about predictability of clinical response outcome. To accomplish these goals we reviewed 103 previously diagnosed cases of low-risk MDS. We found 92% interobserver agreement (P < .001). Sixty-four of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
74
1
8

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(85 citation statements)
references
References 25 publications
2
74
1
8
Order By: Relevance
“…However, partly owing to the uneven distribution of patients, and partly owing to the increased number of subsets still based on the FAB framework, many subgroups are indistinguishable from each other. 11,19-21 Howe et al 21 concluded in their study of the WHO classification that the increased number of diagnostic categories will make application of statistics in studies impossible unless patient groups are extremely large. This raises the question if the sub-categorization of the WHO is based on arbitrary 'splitting' instead of evidencebased 'lumping'.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, partly owing to the uneven distribution of patients, and partly owing to the increased number of subsets still based on the FAB framework, many subgroups are indistinguishable from each other. 11,19-21 Howe et al 21 concluded in their study of the WHO classification that the increased number of diagnostic categories will make application of statistics in studies impossible unless patient groups are extremely large. This raises the question if the sub-categorization of the WHO is based on arbitrary 'splitting' instead of evidencebased 'lumping'.…”
Section: Discussionmentioning
confidence: 99%
“…18 We applied the WHO criteria on a low-risk MDS population and agree with other investigators that, overall, there are significantly different sub-sets for survival and disease evolution. 11,[19][20][21] Multilineage dysplasia in MDS does indeed confer unfavorable survival compared to unilineage dysplasia. However, partly owing to the uneven distribution of patients, and partly owing to the increased number of subsets still based on the FAB framework, many subgroups are indistinguishable from each other.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it is an advance over the FAB classification system, the WHO nomenclature still is based on morphology and blast counts, and whether it can capture the clinical heterogeneity of MDS remains to be seen. 22 The International Prognostic Scoring System (IPSS) is based on the percent of bone marrow blasts, the presence of cytogenetic abnormalities, and the degree of cytopenia (Table 2). 23 It assigns points to each of the factors and divides patients into low, intermediate-1, intermediate-2, and high-risk groups with corresponding median survival times of 5.7 years, 3.5 years, 1.2 years, and 0.4 years, respectively.…”
Section: Classification and Prognostic Factorsmentioning
confidence: 99%
“…By reviewing published series of MDS treated with erythropoietin (EPO) ± granulocyte colony-stimulating factor (G-CSF), we found 11 responses in 41 treated patients with del 5q (Greenberg et al, 1997;Hellstrom-Lindberg et al, 1998;Howe et al, 2004) (Table III). This response to EPO, with or without G-CSF, seemed to be lower in del 5q MDS than in other low-risk MDS.…”
Section: Recombinant Erythropoietin Thalidomide and Retinoidsmentioning
confidence: 99%